Health-related quality of life improvement by adalimumab therapy in patients with rheumatoid arthritis in Taiwan: A nationwide prospective study. Issue 4 (24th January 2023) - Hsieh, Song-Chou; Tsai, Ping-Han; Kuo, Chang-Fu; Cheng, Tien-Tsai; Lai, Ning-Sheng; Lin, Jing-Chi; Lin, Liang-Hung; Tsai, Chang-Youh
Abstract : Background: To determine the effects of adalimumab on health-related quality of life (HRQoL) in Taiwanese patients with moderate-to-severe rheumatoid arthritis (RA) (NCT02616380). Methods: During a 24-week observational period, 100 biologic-naive patients with RA received 40 mg adalimumab subcutaneously, every 2 weeks. The primary endpoint was a change in Health Assessment Questionnaire–Disability Index (HAQ-DI) score at 24 weeks. The secondary endpoints included change in HAQ-DI at week 12, number and percentage of patients achieving a meaningful improvement in HAQ-DI at weeks 12 and 24, and changes in the 36-Item Short Form Health Survey (SF-36), EuroQol 5-dimension 3-level version (EQ-5D-3L) index, and Work Productivity and Activity Impairment (WPAI) questionnaire scores at weeks 12 and 24. Results: At weeks 12 and 24, mean changes in HAQ-DI from baseline were −0.34 ± 0.46 and −0.44 ± 0.59 (both p < 0.001), and clinically meaningful improvement in HAQ-DI was achieved by 60.4% and 59.6% of patients, respectively. SF-36, EQ-5D-3L index, and WPAI scores significantly improved ( p < 0.001) from baseline to weeks 12 and 24. Exploratory analyses showed diabetes was significantly associated with changes in HAQ-DI, EQ-5D-3L, and WPAI scores whereas peptic ulcer correlated with changes in the SF-36 physical component summary T-score. Conclusion: HRQoL improved after initiation of adalimumab therapy in Taiwanese patients with moderate-to-severe RA.